Polyporus Umbellatus Protects Against Renal Fibrosis by Regulating Intrarenal Fatty Acyl Metabolites - Wang, Yan-Ni; Wu, Xia-Qing; Zhang, Dan-Dan; Hu, He-He; Liu, Jian-Ling; Vaziri, Nosratola D.; Guo, Yan; Zhao, Ying-Yong; Miao, Hua (Frontiers in Pharmacology, 2021)
Background: Chronic renal failure (CRF) results in significant dyslipidemia and profound changes in lipid metabolism. Polyporus umbellatus (PPU) has been proven to prevent kidney injury and subsequent kidney fibrosis. Methods: Lipidomics was undertaken to explore the intrarenal lipid metabolic profiling in adenine-induced CRF rats and further investigated the effect of PPU and its main bioactive component ergone on lipid metabolism disorders. Univariate and multivariate statistical analyses were performed for choosing intrarenal differential lipid species in CRF rats and the intervening effect of n-hexane extract of PPU and ergone on CRF rats. Results: Compared with control group, decreased creatinine clearance rate indicated declining kidney function in CRF group. Base on the lipidomics, we identified 65 lipid species that showed significant differences between CRF and control groups. The levels of 12 lipid species, especially fatty acyl lipids including docosahexaenoic acid, docosapentaenoic acid (22n-3), 10,11-Dihydro-12R-hydroxy-leukotriene C4, 3-hydroxydodecanoyl carnitine, eicosapentaenoic acid, hypogeic acid and 3-hydroxypentadecanoic acid, had a strong linear correlation with creatinine clearance rate, which indicated these lipid species were associated with impaired renal function. In addition, receiver operating characteristics analysis showed that 12 lipid species had high area under the curve values with high sensitivity and specificity for differentiating CRF group from control group. These changes are related to the perturbation of fatty acyl metabolism. Treatment with PPU and ergone improved the impaired kidney function and mitigated renal fibrosis. Both chemometrics and cluster analyses showed that rats treated by PPU and ergone could be separated from CRF rats by using 12 lipid species. Intriguingly, PPU treatment could restore the levels of 12 lipid species, while ergone treatment only could reverse the levels of six fatty acids in CRF rats. Conclusion: Impaired intrarenal fatty acyl metabolites were implicated in renal fibrosis. PPU and ergone alleviated renal fibrosis and partially improved fatty acyl metabolism, which revealed that PPU exerted its renoprotective effect by regulating fatty acyl metabolism that might be biochemical mechanism of PPU against renal fibrosis. Therefore, these findings indicated that fatty acyl metabolism played an important role in renal fibrosis and could be considered as an effective therapeutic avenue against renal fibrosis.